THE EFFECT OF ADDING SWEET ORANGE ESSENTIAL OIL IN ANDROMED EXTENDER ON GOAT SPERM MOTILITY - Sitepu, Sukma Aditya; Marisa, Julia; Rianto, Aditiya Amanda (Proceeding International Conference of Science Technology and Social Humanities, 2022)
This study aimed to determine the effect of andromed diluent added with various levels of sweet orange essential oil on buck spermatozoa. Observations were made microscopically, namely by observing the motility of buck spermatozoa. This study hypothesized that adding sweet orange essential oil to andromed diluent could increase and maintain the percentage value of spermatozoa motility in buck semen. The materials used in this study were buck fresh semen, andromed and sweet orange essential oil. The experimental design used in the study was a non-factorial, Completely Randomized Design (CRD) with five treatments and five replications. The treatment added 0%, 0.25%, 0.5%, 0.75%, and 1% sweet orange essential oil. The parameters observed were the motility evaluation of buck spermatozoa. The results showed the motility of spermatozoa with the addition of sweet orange essential oil P0 = 70%, P1 = 70%, P2 = 75%, P3 = 75%, and P4 = 75%. It concluded that the best result and recommended use in Buck Artificial Insemination was the addition of 1% essential oil (P4).